SIMULATION PROCESS OF REMOVING NON-METALLIC INCLUSIONS IN ALUMINUM ALLOYS USING THE PROGRAM FLOW-3D - N. V. Sletova; I. N. Volnov; S. P. Zadrutsky; V. A. Chaikin (Литьë и металлургия)
The perspective materials for making fining preparations for the silumins are the calcium and strontium carbonates from the environmental safety point of view are shown. Principle possibility of using dispersed carbonates in the fining mixtures is confirmed by late inoculation process research using simulation FLOW-3D.The high efficiency of the fining mixture with the inoculants effect is confirmed by the industrial tests